The Degree of Use of Google Applications by Faculty Members at the University of Islamic Sciences by Supervising their Students in Light of the Corona Pandemic - Dania Bashee Arabyat; Othman Naser Mansour; Osama Adel Hasouneh (Deanship of Scientific Research (DSR), the University of Jordan, 2023)
Objectives: The study aimed to know the degree to which faculty members at the International Islamic Sciences University in the Capital Amman Governorate used Google applications by supervising their students in light of the Corona pandemic. Methods: The descriptive approach (survey) was used. The study sample was chosen randomly, as the number of university students reached (3945) male and female students, and the study sample consisted of (371) male and female students. The questionnaire was used as a tool to collect the study data. Results: The study found the following results. The degree to which faculty members at the International Islamic Sciences University in the Capital Amman Governorate use Google applications to supervise their students in light of the Coronavirus pandemic was low, There are no statistically significant differences among the sample members in their estimation of the degree to which faculty members at the International Islamic Sciences University in the Capital Amman Governorate use Google applications to supervise their students in light of the Corona pandemic due to the variables of sex and specialization. Conclusion: The use of Google applications in supervising students was low and not affected by gender and specialization. In light of the results, researchers recommend the following: Training faculty members and providing them with the skills to employ these applications in the process of supervising their students, and to activate all applications provided by Google to serve students and not be limited to one application.